2013
DOI: 10.1371/journal.pone.0064209
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Donors with Controlled Reperfusion after Sixty Minutes of Asystole: A Novel Reliable Resource for Kidney Transplantation

Abstract: BackgroundOrgan shortage leads to usage of kidneys from donors after sudden cardiac death, or uncontrolled donors (UDCD). Ischemic injury due to cessation of circulation remains a crucial problem that limits adoption of UDCD. Our clinical investigation was to determine the applicability of kidneys obtained from UDCD and resuscitated by extracorporeal perfusion in situ after 60 minutes of asystole.MethodsIn 2009–2011, organ procurement service of St. Petersburg, obtained kidneys from 22 UDCD with critically exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 44 publications
0
37
1
9
Order By: Relevance
“…With ECPR return of circulation is achieved after periods of CA long enough to allow for intravascular coagulation causing the no-reflow phenomenon, and thus the potential for improving reperfusion could be maximized with thrombolytic agents. Streptokinase pre-flush during ex situ and in situ perfusion of kidneys from donors after cardiac death (DCD) has been shown to improve function of transplanted organs after up to 60 minutes of asystole [26, 27]. Organs transplanted after in situ perfusion during DCD procurement undergo the same pathophysiological events of ischemia-reperfusion as organs resuscitated after prolonged CA including the possible occurrence of no-reflow phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With ECPR return of circulation is achieved after periods of CA long enough to allow for intravascular coagulation causing the no-reflow phenomenon, and thus the potential for improving reperfusion could be maximized with thrombolytic agents. Streptokinase pre-flush during ex situ and in situ perfusion of kidneys from donors after cardiac death (DCD) has been shown to improve function of transplanted organs after up to 60 minutes of asystole [26, 27]. Organs transplanted after in situ perfusion during DCD procurement undergo the same pathophysiological events of ischemia-reperfusion as organs resuscitated after prolonged CA including the possible occurrence of no-reflow phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al demonstrated that intravenous thrombolytic therapy given during CPR reduces the brain no-reflow phenomenon in animals after prolonged cardiac arrest [25]. Recent studies of organ in vivo perfusion for donation after cardiac death (DCD) have demonstrated that addition of thrombolytic agents to the initial perfusate enhances the function of transplanted organs [26, 27]. Since in vivo perfusion for DCD is typically performed after prolonged durations of untreated CA, we hypothesized that a similar strategy would be effective in ECPR.…”
Section: Introductionmentioning
confidence: 99%
“…Сегодня их называ-ют органами, полученными от доноров с расширен-ными критериями (ДРК) [17,18]. К ним относятся доноры со смертью мозга старшей возрастной груп-пы, с сопутствующими заболеваниями, в том числе с артериальной гипертензией и сахарным диабетом, а также погибшие в результате внезапной необра-тимой остановки кровообращения, или асистоли-ческие доноры (АСД) [19][20][21][22]. Внезапно умершие пациенты представляются перспективным ресур-сом трансплантации.…”
Section: Normothermic Extracorporeal Perfusion In Situ In Deceased Orunclassified
“…Поскольку пере садка печени является «хирургией одного шанса», то повышаются требования к методам верификации качества трансплантата перед операцией. Мини мизация нежелательных изменений в донорском органе могла бы быть достигнута за счет создания перфузионных устройств, с помощью которых воз можно проведение искусственного кровообраще ния для селекции, «лечения» и поддержания жиз неспособности in situ и ex vivo [4,6,7,10,12,13].…”
Section: Introductionunclassified